2021
DOI: 10.1097/cad.0000000000001254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin use on the risk and prognosis of colorectal cancer in diabetes mellitus: a meta-analysis

Abstract: Whether metformin is a protective factor of colorectal cancer (CRC) among CRC patients is still not entirely clear. Thus, we conducted this systemic review and metaanalysis to provide a comprehensive review of associations between metformin therapy and CRC risk or survival outcomes for clinical decisions. Articles published before July 2021 were searched in databases (PubMed and Web of Science). Odds ratio (OR)/risk ratio (RR) or hazard ratio (HR) and their confidence intervals (CIs) were computed using STATA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…Three recent meta-analyses of observational data confirm a beneficial effect of metformin on the incidence of CRC, all-cause mortality of CRC and lower CRC-specific mortality. An 2021 meta-analysis of 28 studies including over 2 million people showed that the use of metformin reduced the risk of CRC by 29% compared with nonuse (OR/RR = 0.71, 95% CI, 0.64–0.80) [ 84 ]. This finding was in line with two 2020 meta-analyses which found a reduced incidence of CRC in diabetic patients of 12% (adjusted RR 0.88, 95% CI 0.83–0.94) [ 91 ] and 24% (RR 0.76, 95% CI 0.69–0.84) [ 92 ].…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Three recent meta-analyses of observational data confirm a beneficial effect of metformin on the incidence of CRC, all-cause mortality of CRC and lower CRC-specific mortality. An 2021 meta-analysis of 28 studies including over 2 million people showed that the use of metformin reduced the risk of CRC by 29% compared with nonuse (OR/RR = 0.71, 95% CI, 0.64–0.80) [ 84 ]. This finding was in line with two 2020 meta-analyses which found a reduced incidence of CRC in diabetic patients of 12% (adjusted RR 0.88, 95% CI 0.83–0.94) [ 91 ] and 24% (RR 0.76, 95% CI 0.69–0.84) [ 92 ].…”
Section: Cancermentioning
confidence: 99%
“…With regard to prognosis of CRC patients, an all-cause mortality benefit was reported of 28% (HR 0.72, 95% CI 0.62–0.83) and CRC-specific mortality of 20% (HR 0.80, 95% CI 0.70–0.92) [ 84 ]. Another meta-analysis reported reduced all-cause mortality rates of 40% (HR 0.60, 95% CI 0.53–0.67) and CRC specific rates of 34% (HR 0.66, 95% CI 0.59–0.7) [ 92 ].…”
Section: Cancermentioning
confidence: 99%
“…34 These differences may be mainly driven by the study design. Of note, these meta-analyses 12,36 did not analyze Black or any other racial/ethnic group as a separate group. A more recent metaanalysis in the relation between metformin and colorectal cancer reported that metformin may be a protective factor for colorectal cancer.…”
Section: Metformin Use and Prostate Colorectal And Breast Cancers And...mentioning
confidence: 99%
“…A more recent metaanalysis in the relation between metformin and colorectal cancer reported that metformin may be a protective factor for colorectal cancer. 36…”
Section: Metformin Use and Prostate Colorectal And Breast Cancers And...mentioning
confidence: 99%
“…Mounting evidence indicates a potential role of metformin in prevention and improve prognosis (Bradley et al, 2018; Higurashi et al, 2016; Hosono et al, 2010; Liu et al, 2017; Ng et al, 2020; Sehdev et al, 2015; Singh et al, 2013). For example, a recent meta-analysis reported metformin use decreased the risk of CRC in T2D patients by 29% and reduced both all-cause mortality of CRC in T2D and CRC-specific mortality in T2D(Wang and Shi, 2021). Furthermore, in in vitro models of CRC, metformin has shown synergistic effects with oxaliplatin (Richard and Martinez Marignac, 2015), cisplatin (Zhang et al, 2020), irinotecan (Khader et al, 2021), and fluorouracil (Sang et al, 2020), highlighting metformin as a potential sensitization agent to CRC chemotherapy.…”
Section: Introductionmentioning
confidence: 99%